IMPLEMENTASI ONE ROOF SYSTEM DI PENGADILAN PAJAK: TANTANGAN DAN SOLUSI DALAM MEWUJUDKAN PERBAIKAN PENYELESAIAN SENGKETA PAJAK - Budiono, Doni (Jurnal Yuridis, 2024)
Constitutional Court Decision Number 26/PUU-XXI/2023 concerning "one roof system" in the Tax Court is a sign ificant milestone in achieving justice for tax payers. This decision reaffirms the essence of the Tax Courtand the Supreme Court as judicial institutions seeking justice, not merely as tools for the government tosecure statere venue. The issuanceof thisdecisionserves as a The issuance of this decisionserves means of reform to address issues in tax dispute resolution from the Directorate General of Taxes (DJP) level, theTax Court, to the Supreme Court. This study discusses two main research questions: First, whether the issuanceofthe Constitutional Court Decision Number 26/PUU-XXI/2023 on the "one roof system" in the Tax Court issufficientto provide justice for tax payers. Second, what are theis suesfaced in tax dispute resolution from the DJP level, the Tax Court, to the Supreme Court, and their solutions. This research is normative, using statutory, conceptual, and comparative legal approaches. The research result sindicate that the implementation of the "one roof system" in the Tax Court has a positive impact on the transparency and accountability of the tax dispute resolution process. However, the implementation of this system alone is not sufficient. There are still various challenges that need to be addressed to fully realizejustice for those seeking it in the tax dispute resolution system.